Interstellar scintillation as the origin of the rapid radio variability of the quasar J1819+3845 - Dennett-Thorpe, J.; de Bruyn, A. G. (Nature (London), 2002)
The liberation of gravitational energy as matter falls onto a supermassive black hole at the centre of a galaxy is believed to explain the high luminosity of quasars. The variability of this emission from quasars and other types of active galactic nuclei can provide information on the size of the emitting regions and the physical process of fuelling the black hole. Some active galactic nuclei are variable at optical (and shorter) wavelengths, and display radio outbursts over years and decades. These active galactic nuclei often also show faster intraday variability at radio wavelengths 3 , 4 . The origin of this rapid variability has been extensively debated 5 , but a correlation between optical and radio variations in some sources 6 , 7 suggests that both are intrinsic. This would, however, require radiation brightness temperatures that seem physically implausible, leading to the suggestion that the rapid variations are caused by scattering of the emission by the interstellar medium inside our Galaxy 8 , 9 . Here we show that the rapid variations in the extreme case of quasar J1819+3845 (ref. 10 ) indeed arise from interstellar scintillation. The transverse velocity of the scattering material reveals the presence of plasma with a surprisingly high velocity close to the Solar System.